Peran Konten Kreatif dalam Meningkatkan Brand Awareness Sopiri Driving School melalui Media Sosial - Rahma Putra Kusdarmawan; Irdha Yunianto; Nuris Dwi Setiawan (UNIVERSITAS STEKOM, 2025)
The development of digital technology has transformed how businesses build brand image through social media. This study aims to determine the role of creative content in enhancing the brand awareness of Sopiri Driving School through social media platforms such as Instagram and TikTok. The research method used is Research and Development (R&D) adapted from the Borg & Gall model, consisting of problem identification, design, development, testing, and evaluation stages. The study produced two promotional videos of 30 seconds each. The results showed that implementing creative content with storytelling and dynamic visuals significantly increased brand awareness. Trial data revealed that social media followers increased by more than 90%, and the engagement rate rose from 3.5% to 8.2% after the content was published. Moreover, 83% of survey respondents stated they recognized Sopiri Driving School after watching the promotional videos. The study concludes that creative content plays an essential role in building a professional brand image and attracting audiences through social media. An effective content strategy not only serves as a promotional tool but also as an interactive communication medium that strengthens the emotional bond between the brand and its audience.